A generic arboviral model framework for exploring trade-offs between vector control and environmental concerns. (7th April 2020) - Suarez, Gonzalo P.; Udiani, Oyita; Allan, Brian F.; Price, Candice; Ryan, Sadie J.; Lofgren, Eric; Coman, Alin; Stone, Chris M.; Gallos, Lazaros K.; Fefferman, Nina H.
Highlights: Public concern about pesticides affect vector-borne disease management outcomes. Public health actions should balance environmental versus disease risks. Mosquito control efforts should involve public outreach to be most effective. Graphical abstract: Abstract: Effective public health measures must balance potentially conflicting demands from populations they serve. In the case of infectious disease risks from mosquito–borne infections, such as Zika virus, public concern about the pathogen may be counterbalanced by public concern about environmental contamination from chemical agents used for vector control. Here we introduce a generic framework for modeling how the spread of an infectious pathogen might lead to varying public perceptions, and therefore tolerance, of both disease risk and pesticide use. We consider how these dynamics might impact the spread of a vector-borne disease. We tailor and parameterize our model for direct application to Zika virus as spread by Aedes aegypti mosquitoes, though the framework itself has broad applicability to any arboviral infection. We demonstrate how public risk perception of both disease and pesticides may drastically impact the spread of a mosquito-borne disease in a susceptible population. We conclude that models hoping to inform public health decision making about how best to mitigate arboviral disease risks should explicitly consider the potential public demand for, or rejection of, chemical control of mosquito populations.